Evaluation of Women's Volleyball Coaching Program on Student Sports Training Education Center in Musi Banyuasin Indonesia - firmansyah, angga; Rahayu, Setya; Nasuka, Nasuka (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
The development of volleyball on Student Sports Training Education Center (PPLPD) in Musi Banyuasin South Sumatra Indonesia its achievement is less stable, therefore it is necessary to conduct an evaluation as a reference for the preparation of further performance coaching programs. The purpose of this study is to evaluate the Context, Input, Process and Product of the PPLPD Musi Banyuasin Volleyball Achievement coaching program. This study used a qualitative approach with the CIPP evaluation model. Data collection techniques used interviews, observation and documentation. Results: Context Program is coaching women's volleyball achievement. Input coach has coaching license, athletes have skills. Facility and infrastructure for volleyball is already good, the sport Centre has national standards, athlete coaching program funds come from Local Government Budget (APBD). Process, having a training program, in which it is controlled, is given monthly coaching funds to coaches and athletes. Product the PPLPD Musi Banyuasin volleyball performance coaching program has not been maximized, only in the top five in the National Championship level between PPLP. The conclusions of this study are: Context Program for the coaching of women's volleyball sports achievements at Musi Banyuasin PPLPD. Input coaches and athletes are in accordance with what was determined by Sports and Youth Office (DISPORA), coaching funds come from APBD. Process the implementation of coaching program is going well. Product coaching program is the result of competition shows unstable or less than optimal performance.